2003
DOI: 10.1046/j.1525-1438.2003.13389.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of frozen section diagnosis in ovarian tumors: Is there a change in the course of time?

Abstract: A retrospective study of 222 ovarian biopsy results between January 1, 2000 and August 31, 2002 was examined to determine the accuracy of frozen section diagnosis. In addition we reviewed all previous studies that examined the accuracy rates of frozen section diagnosis in ovarian tumors. Histopathologic examination results of frozen section biopsies were concordant with paraffin diagnosis in 92% of all cases. The sensitivity rates for benign, malignant, and borderline ovarian tumors were 98%, 88.7%, and 61%, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
4
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 20 publications
(25 reference statements)
7
53
4
3
Order By: Relevance
“…Our study analysis done on 30 patients' shows that test fared well on all 4 conventional indices (sensitivity, specificity, and predictive values) in benign and malignant tumors. Sensitivity for benign tumors in our study is 100%.sensitivity rates reported in the literature are 98 to 99% [10,11,12] . only 1 out 20 diagnosed as benign on frozen section turned out to be borderline on final histopathology.…”
Section: Discussionsupporting
confidence: 48%
“…Our study analysis done on 30 patients' shows that test fared well on all 4 conventional indices (sensitivity, specificity, and predictive values) in benign and malignant tumors. Sensitivity for benign tumors in our study is 100%.sensitivity rates reported in the literature are 98 to 99% [10,11,12] . only 1 out 20 diagnosed as benign on frozen section turned out to be borderline on final histopathology.…”
Section: Discussionsupporting
confidence: 48%
“…Our study showed a false positive rate of 0.4 % and false negative rate of 7.7 %. Literature search shows false positive rates ranging from 2.2 to 10.7 % and false negative rates ranging from 5.4 to 29.3 % [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…According to Gol M et al histological examination of frozen section biopsies was concordant with final histopathological report in 92% cases. 9 Frozen section examination of mucinous tumours showed higher under diagnosis rates in 20%. The availabilty of oncosurgeon while operating cases of suspected malignancy has to be emphasized.…”
Section: Discussionmentioning
confidence: 99%